Diamond Head Drill Communication, Easier Leadership, and Incentives as Drivers of Hospital Competitiveness: The Mediating Role of Performance in West Java Public Hospitals - Bambang Sumardi; Sri Widiyastuti; Derriawan (PT. Berkah Digital Teknologi, 2026)
Purpose — This study examines how Diamond Head Drill (DHD) communication, EASIER leadership, and incentives influence hospital performance and, in turn, how performance affects the competitiveness of public regional general hospitals (RSUD) in West Java, with performance tested as a mediating mechanism. Research method— A quantitative, cross-sectional survey design was applied and analyzed using AMOS-based Structural Equation Modeling (SEM). Data were collected from 397 medical, non-medical, and managerial staff across ten RSUD in West Java Province. Result— DHD communication, EASIER leadership, and incentives each showed positive and significant effects on hospital performance (β = 0.516; 0.273; 0.494; p < 0.05). Performance had a strong and significant effect on competitiveness (β = 0.436; p < 0.001). DHD communication also had a significant direct effect on competitiveness (β = 0.546; p < 0.001), whereas the direct effects of EASIER leadership and incentives on competitiveness were positive but not significant (β = 0.095; 0.119; p > 0.05). Mediation testing indicates performance functions as a key mediator, particularly for incentives (indirect effect = 0.215; p < 0.05). Conclusion— Competitiveness improvements in West Java RSUD are primarily achieved through strengthening internal performance. DHD communication contributes both directly to competitiveness and indirectly via performance, while EASIER leadership and incentives enhance competitiveness mainly when they first improve performance outcomes. Practically, RSUD management and local governments should (i) institutionalize DHD communication into clinical and cross-unit SOPs, (ii) invest in adaptive/participative leadership development, and (iii) redesign incentive systems to be transparent and explicitly performance-linked to accelerate service quality, efficiency, and public trust as broader social benefits.